Bridging Divides: Lived Experiences of School Heads in Conflict Management - Espeño, Sheena R. (Edukhasi: Jurnal Inovasi Pendidikan, 2025)
This study aimed to explore the practices of school heads in handling conflicts among their teachers in the City Schools Division of Cabuyao during the school year 2024-2025. There were ten (10) school heads; five (5) of each from public elementary and secondary schools who took part as the participants of the study. The researcher utilized the descriptive-qualitative research design and researcher-made questionnaire to assess and measure the variables under study. The statistical tools used to analyze the data gathered were through thematic approach where themes emerged correspondingly. Findings revealed the (10) themes which were Expectations Gap, Emotional Management and Conflict Resolution in Leadership, Respectful Communication, Communication Barriers, Equitable Communication, Leadership Growth Through Conflict Resolution, Transparent Collaboration, Stakeholder Collaboration, and Growth through Resolution. It was concluded that Emotional Management and Conflict Resolution in Leadership revealed that school heads’ emotional responses vary depending on the nature of the conflicts they face. However, Communication Barriers emerged as a major challenge in managing conflicts and maintaining a harmonious school environment. The study also found that Leadership Growth Through Conflict Resolution plays a critical role in shaping the leadership styles of school heads. Lastly, Growth through Resolution demonstrated that school heads' professional development and perspectives evolve through conflict resolution experiences.To ensure a more efficient output, implementation of series of trainings and seminars to  promote leadership, implementing programs that promote mental health awareness, anti-bullying campaigns, and diversity and inclusion initiatives, and promoting open, transparent, and respectful communication through structured dialogue sessions, mediation programs, and conflict resolution workshops were few of the recommendations. For future researchers, other school heads from neighboring divisions may be studied along with different possible moderating variables that may illuminate various practices in handling school conflict.